Revolutionizing Collaboration: HoloSync 5G's Real-Time Holographic Magic - Jadhav, Rahul Jalinder; Sekhar, G Chandra; Devghare, Khushal; Devi, Laiphrakpam Jibanpriya; R, Aarthi; Ramesh, R (2025 International Conference on Data Science, Agents & Artificial Intelligence (ICDSAAI), 2025)
The HoloSync 5G Hybrid Model represents a groundbreaking solution for real-time holographic communication, integrating 5G infrastructure, advanced machine learning techniques, and dynamic compression algorithms. This model designed to address the challenges of high latency, bandwidth constraints, and rendering inconsistencies in global remote collaboration. The system leverages Multi-Access Edge Computing (MEC) for low-latency data processing, while adaptive encoding and decoding ensure seamless data transmission. Experimental results demonstrate a 44% reduction in latency and a 41% improvement in bandwidth utilization compared to baseline systems. Rendering fidelity significantly enhanced, with a 9.41% increase in SSIM (0.93) and 11.78% improvement in PSNR (42.7 dB). User satisfaction ratings average 4.8/5, reflecting the intuitive design and clarity of the holographic experience. Scalability testing confirmed consistent performance, even in sessions with up to 50 users. These results validate the HoloSync model as a robust and efficient platform for applications such as telemedicine, remote education, and industrial collaboration. The study concludes with promising insights into the potential of hybrid intelligence and 5G advancements to redefine real-time holographic communication.